MOTIVASI BELAJAR SISWA KELAS V TERHADAP MATA PELAJARAN PKN DI MI MA’ARIF GANDU DESA GANDU KECAMATAN MLARAK KABUPATEN PONOROGO - Ambiro Puji Asmaroini (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2017)
Abstract: This study aims to understand the motivation of students in class V on Civic Education subjects at MI Ma'arif Gandu, Gandu Village, Mlarak Subdistrict, Ponorogo Regency and efforts and solutions to motivation problems. The method used is descriptive qualitative. The results show that in school, grade V students in MI Ma'arif enjoy the average subject of Citizenship Education. Based on the examination result of some students the value is below the minimum mastery criteria but not half to between 5-7 among 26 students. The value is not complete because at home students less attention in learning, students who pay less attention when in teaching in the classroom, and the condition of children who are less normal. At home the child is not considered in learning because of family factors. Efforts and solutions that teachers do at school include: to ask questions to students who do not open the book at the time of learning, teachers do question and answer directly to students related to the material. Teacher gives pearl words during learning activities. Another effort is to collect the student guardian at the time of semester division report